Análise geoambiental dos ambientes da planície aluvial do alto curso do rio paraná: Fragilidade e impactos ambientais relativos ao desenvolvimento do uso turístico - Galvão, Valdecir; Stevaux, José CâNdido; Saad, Antonio Roberto (My University, 2014)
Brazil has the largest water reserves in the world that represents about 16[%] of world reserves, which include the largest surface water resources and groundwater (aquifers). Tourism activities in riverine environments have been developing rapidly in all regions of Brazil. In the southeast, south and center-west of Brazil, its main river, the Paraná River, has one of the largest hydropower potential in the world, holds numerous hydropower plants (UHT) including UHT Itaipu, the largest in the country. The study area is located near the triple border of Mato Grosso do Sul, Paraná and São Paulo, in the municipalities of Puerto Rico and St. Peter of Paraná (Port District San José), Marilena and Querencia in Northern Paraná State. The various tourist activities in the region use different subambientes the floodplain of the Paraná River, developing river tourism and fishing tourism. With the relatively recent growth of tourism in the region, it is believed that tourism will intensify even further to the point of endangering the entire ecosystem of the floodplain, requiring studies on the environmental fragility and their potential impacts to the local and its surroundings. In this context, this work has as main goal, develop a geo-environmental analysis of the high Paraná River in the states of Mato Grosso do Sul and Paraná, in order to identify and characterize the most favorable river subambientes the tourist interest, determine what the environmental fragility of the area and what time of resilience that have subambientes, identifying the impacts may result from tourist activity with the purpose of tourism development with minimal impact.
Geoenvironmental analysis of the floodplain environments of the upper course of the Parana River: Fragility and environmental impacts related to the development of tourist use
Keywords: Environmental fragility; Floodplain; Impacts of tourism; Paraná River; Tourism